Stillbirths in Jordan: rate, causes, and preventability. (17th April 2020) - Khader, Yousef S.; Batieha, Anwar; Khader, Albaraa; Hamadneh, Shereen
Abstract: Objectives: This study aimed to determine the stillbirth rate in Jordan and to determine the leading causes of stillbirths. Analyzing the stillbirth data from a large sample size of Jordanian women would be very valuable for planning the resources and improving the services. Methods: The data from the national study of perinatal mortality in Jordan were analyzed. A total of 21, 980 women who delivered at a gestational age ≥20 weeks in any of the 18 selected hospitals during the study period (March 2011–April 2012) were analyzed. The stillbirth rate was calculated as the number of stillbirths per 1000 total births. The deaths were also classified according to NICE classification system. Results: The rates of stillbirths were 11.6/1000 total births born after 20 weeks of gestation, 11.2/1000 total births born ≥22 weeks of gestation, 10.6/1000 total births born ≥24 weeks of gestation, and 9.0/1000 total births born ≥28 weeks of gestation. According to NICE classification, the main causes of stillbirths were maternal diseases (19.5%), unexplained immaturity (18.8%), congenital anomalies (17.6%), unexplained antepartum stillbirths (17.6%), obstetric complications (8.4%), placental abruption (5.7%), and multiple births (5%). The expert Panel judged that 34.5% of all fetal deaths were preventable and 30.3% were possibly preventable with optimal care. Conclusions: This study highlighted stillbirth risks in Jordan, which could encourage maternal–infant health-care providers, other researchers, policymakers, and stakeholders to implement solutions and to develop a feasible intervention.